Pengaruh Pemberian Cone Drill Exercise Terhadap Tingkat Kelincahan Pada Pemain Futsal Usia 19 -21 Tahun - SETIONINGSIH, INDAH; , Sugiono, S.Fis., M.H (Kes); , Isnaini Herawati, S.Fis, M.Sc (2016)
Background: The agility is one of motor components required for all activities involving the speed of the body movement. It plays significant roles in the movement of the Futsal players, such as chasing or avoiding opponents, and reacting towards the movement of the ball. Cone drill exercise can be used to improve the agility of the male Futsal players aged 19-21. Objective: The research aims to identify the effect of cone drill exercise towars the agility level of the male Futsal players aged 19-21. Methods: This research employed a quasi experimental method which design was one group pretest-posttest with Group Control Design. The samples of the treatment group were given cone drill training of 6 minutes' duration, performed 3 times a week for 4 wees. The agility was measured by performing 10 meters-shuttle run test in which a stopwatch was used as the parameter. The technique of data analysis was a Shapiro Wilk test, which used a paired sample t-test to examine the influence of the agility level of the Futsal players. The Findings: Of the research show that P-value obtained in both treatment and controlled groups is 0,000. Furthermore, there are different effects after the statistical test was performed by using paired sample t-test, in which p-value is 0,00. Conclusion: The cone drill exercise has effects on the agility level of the male futsal players aged 19-21.